2021
DOI: 10.1021/acs.analchem.1c01099
|View full text |Cite
|
Sign up to set email alerts
|

Development of Crime Scene Intelligence Using a Hand-Held Raman Spectrometer and Transfer Learning

Abstract: The classification of ignitable liquids, such as gasoline, is critical crime scene intelligence to assist arson investigations. Rapid field gasoline classification is challenging because the current forensic testing standard requires gas chromatography–mass spectrometry analysis of evidence in an accredited laboratory. In this work, we reported a new intelligent analytical platform for field identification and classification of gasoline evidence. A hand-held Raman spectrometer was utilized to collect Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“… 12 Huang et al also used a transfer learning method based on a GoogLeNet model for the field identification and classification of gasoline evidence. 13 Ho et al applied CNN-based deep learning approaches to accurately identify 30 common bacterial pathogens. 14 Deng et al proposed a method that can learn multi-scale features using the automatic combination of multi-receptive fields of convolutional layers.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Huang et al also used a transfer learning method based on a GoogLeNet model for the field identification and classification of gasoline evidence. 13 Ho et al applied CNN-based deep learning approaches to accurately identify 30 common bacterial pathogens. 14 Deng et al proposed a method that can learn multi-scale features using the automatic combination of multi-receptive fields of convolutional layers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Huang's group applied continuous wavelet transformation to convert Raman spectra into images and then introduced GoogLeNet to discriminate the converted images through transfer learning. [ 29 ] However, in both of above works, the number of calibration data in training set was no less than twice that in test set. In this study, it is found that the 1D‐CNN performed better than KNN when using only 75% calibration data for retraining, which is a fresh contribution of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of unknown substances is critical in many fields such as food product quality control, 1 pharmaceutical drug characterization, 2 forensic investigation, 3 and bacterial detection. 4 Raman spectroscopy is often used in these applications 2–4 as a low-cost, non-invasive technique. Raman spectroscopy provides a chemical fingerprint by using scattered light to probe the vibrational modes of a sample.…”
Section: Introductionmentioning
confidence: 99%